Clinical Relevance of Tubular Breast Carcinoma: Large Retrospective Study and Meta-Analysis - Metovic, Jasna; Bragoni, Alberto; Osella-Abate, Simona; Borella, Fulvio; Benedetto, Chiara; Gualano, Maria Rosaria; Olivero, Elena; Scaioli, Giacomo; Siliquini, Roberta; Ferrando, Pietro Maria; Bertero, Luca; Sapino, Anna; et al. (Frontiers in Oncology, 2021)
Background: Tubular carcinoma (TC) is a low proliferative grade 1 (G1) breast cancer (BC). Despite its favorable outcome and allegedly lower aggressiveness, patients are treated like other luminal G1 BC, with radiotherapy (RT) and hormonal therapy (HT). We performed: (1) a retrospective study comparing a TC cohort and a control series of luminal G1 BC and (2) a systematic review and meta-analysis focused on TC outcome. Materials and Methods: We selected a series of 572 G1 luminal BC patients [111 TC, 350 not otherwise specified (NOS), and 111 special-type (ST) BC] with follow-up and clinico-pathological data, who underwent local excision followed by RT at Città della Salute e della Scienza Hospital, Turin. Moreover, 22 and 13 studies were included in qualitative and quantitative meta-analysis, respectively. Results: TCs were generally smaller (≤10 mm) (P < 0.001), with lower lymph node involvement (P < 0.001). TCs showed no local and/or distant recurrences, while 16 NOS and 2 ST relapsed (P = 0.036). Kaplan–Meier curves confirmed more favorable TC outcome (DFI: log-rank test P = 0.03). Meta-analysis data, including the results of our study, showed that the pooled DFI rate was 96.4 and 91.8% at 5 and 10 years, respectively. Meta-regression analyses did not show a significant influence of RT nor HT on the DFI at 10 years. Conclusions: Compared to the other G1 BCs, TCs have an excellent outcome. The meta-analysis shows that TC recurrences are infrequent, and HT and RT have limited influence on prognosis. Hence, accurate diagnosis of TC subtype is critical to ensuring a tailored treatment approach.